UPAYA GURU ALQURAN HADIS DALAM MENGATASI KESULITAN MEMBACA ALQURAN SISWA KELAS VII MTs AL-MA’RUF DENPASAR - Umroh, Umroh; Arjiman, Arjiman (Widya Balina, 2024)
Difficulty reading the Qu’ran in students will usually be obvious. With the emergence of unusual behavior, one of them is difficulty in reading the Qu’ran. So the efforts of Al-Quran Hadith teachers in overcoming difficulties in reading the Al-Quran in class VII at MTs Al-Ma'ruf Denpasar are very much needed in overcoming students' difficulties. Based on the problems above, the focus of the research is: 1) What difficulties do students experience in reading the Koran? 2) How do Al-Quran Hadith teachers try to overcome students'difficulties in reading the Al-Quran? 3) What are the supporting and inhibiting factors for Al Quran Hadith teachers in overcoming difficulties in reading the Al-Quran? The aims of this research are 1) To find out what difficulties students experience in reading the Qur’an, 2) Efforts of Al-Quran Hadith teachers in overcoming difficulties in reading the Al Quran 3) Supporting and inhibiting factors for Al-Quran Hadis teachers in overcoming difficulties in reading the Al-Quran. This type of research is qualitative with a descriptive approach,informants are determined purposively. The informants are the head of the madrasah, Alquran Hadis teacher, class VII students and parents. Data is collected by interviews, observation and documentation, then analyzed using the stages of data reduction and presentation. data and drawing conclusions The research results show that 1) Difficulties in reading the Qur’an include: difficulty in pronouncing makharijul letters, difficulty applying the laws of reciting tajwid, difficulty in recognizing punctuation, not knowing the length and shortness of reading the Qur’an and lack of fluency in reading the Qur’an. 2) The Al-Quran Hadith teacher's efforts to overcome difficulties in reading the Al-Quran are by making morning recitations of the Al-Quran, arousing students' interest in reading, providing encouragement and motivation, selecting and developing learning methods and providing good role models. 3) Supporting factors for teacher efforts in overcoming difficulty reading the Koran, there is guidance to read the Koran every morning, supporting facilities and infrastructure. The inhibiting factors for teachers in overcoming student difficulties include: low student interest and also family factors.